Going for Gaps in Glaucoma - Kolko, Miriam; Cvenkel, Barbara (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Glaucoma is a major cause of blindness that can be prevented if detected and treated in the early stages of the disease. This reprint includes original research studies and reviews that focus on strategies to help identify and treat patients with glaucoma more effectively, improve their treatment adherence, review the potential impact of psychopharmacological therapy on intraocular pressure, and increase knowledge of potential treatment targets for neuroprotection.